Paradoxy úspěšné teorie: intersekcionalita mezi kritikou a stvrzováním hegemonie - Kateřina Kolářová (Gender a Výzkum)
This text traces the recent critical debates within intersectional theory. It foregrounds the critiques that point out the power dynamics underwriting the success of intersectional theory and it focuses on the critiques of the racialised dynamics in the current development of intersectional work and in the shift from the intersectional politics of ‘redress’ towards the agenda of inclusivity and diversity. The review of these lines of critique seeks to serve as a critical platform against which to contextualise the recently growing interest in intersectionality in the Czech republic.